Monitoring and Evaluation Preparedness of Public Sector Institutions in South Africa - Eresia-Eke, C.E.; Boadu, E.S. (Journal of Reviews on Global Economics, 2019)
In a bid to improve service delivery in South Africa, the government has created a government-wide monitoring and evaluation (M&E) system that would help gauge performance across all spheres of government. This has compelled public sector institutions to adopt and implement M&E systems mandatorily, even when they are not necessarily ready for it. The unpreparedness inevitably perforates the ability of M&E systems to credibly support performance improvement in public sector institutions and it is problematic. To some extent, the practice of M&E in the public sector seems to be for purposes of compliance rather than the ideal of performance improvement. This qualitative study investigates the readiness of South African public sector institutions for M&E, through the perspectives of Managers primarily in the M&E space. Findings reveal mixed signals of M&E readiness. For instance, the factors motivating the creation of the M&E system and the calibre of staff championing it, seem to suggest M&E readiness. Conversely, the non-availability of capacity to support the system and the potential response of staff to negative information generated by M&E signal non-readiness. The import of this is that readiness assessments specific to institutions have to be conducted as a basis for determining areas where the prerequisites for M&E are lacking. This should then inform remedial efforts that ultimately help to improve the potency of the M&E system.